RESPON FISIOLOGIS DAN PSIKOLOGIS PADA MAHASISWA PASCA TERPAPAR COVID-19 - Kasiati; Devi Firdaus Puspita Sari (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2023)
The COVID-19 pandemic is increasing day by day, causing many responses experienced by an individual, especially in post-covid-19 patients. It’s physiological and psychological responses. Physiological response is an individual response physically which is characterized by symptoms of body abnormalities, while the psychological response is something that can be seen or will happen in a person, both positive and negative things. Psychological responses experienced are such as anxiety and depression. This study aims to determine how much physiological and psychological responses such as anxiety and depression are experienced by post-covid-19 patients at the Department of Nursing, Health Polytechnic Of Kemenkes Malang. This research technique uses quantitative methods with a descriptive research design. The research sample was taken using a total sampling technique with a total of 30 respondents. The instruments used are physiological response questionnaires, anxiety questionnaires and depression questionnaires. The results showed that post-covid-19 patients whose physiological response was disturbed were 10 students (33,3.7%), and 20 students were not disturbed (66,7%). And post-covid-19 patients who experienced mild anxiety as many as 16 people (53%), moderate anxiety as many as 5 student (17%) while normal/not anxious as many as 9 student (30%). For patients with mild depression as many as 17 student (57%), moderate depression as many as 3 student (10%), while not depressed / normal as many as 10 student (33%). For further research, it is expected to develop research on appropriate interventions for post-covid-19 patients so that in the future they do not experience a more severe physiological and psychological responses.